PENGARUH LEVERAGE, PROFITABILITAS, DAN FIRM SIZE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SUBSEKTOR JASA PEMBIAYAAN PERIODE 2020-2024 - Mike Fernisia (Universitas Trilogi, 2025)
Tax avoidance is a crucial issue in the business world, as it can affect state tax revenues and reflect a company’s level of compliance with tax regulations. The purpose of this study is to examine and analyze the effect of Leverage, profitability, and Firm size on tax avoidance in companies within the financing services subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. This study uses a quantitative approach with descriptive and verificative methods. The sample was selected using purposive sampling and resulted in 10 companies that met the criteria. The data used is secondary data in the form of annual financial statements, and the analysis method employed is multiple linear regression with the assistance of SPSS version 27. The results show that Leverage and profitability have a significant positive effect on tax avoidance, while Firm size has no significant effect, although it shows a positive direction. These findings support agency theory and trade-off theory in explaining corporate tax avoidance behavior. Keywords: Firm size, Leverage, Profitability, Tax Avoidance